Analisis Batako Dengan Campuran Serbuk Kaca Sebagai Pengganti Pasir - Rahmat Rahmat; Irna Hendriyani; Risma Sa’diyah (Media Ilmiah Teknik Sipil, 2020)
One of the innovations in the use of glass waste in the construction sector is as a mixture of concrete brick. In this research glass dust from a building demolition in the Klandasan area of ​​Balikpapan was used as a substitute for sand in a mixture of concrete brick. This research aims to analyze the use of glass powder as a substitute for sand in a mixture of concrete brick based on SNI 03-0349-1989. Concrete brick specimens are made with a cement and sand ratio of 1: 6. The variation in the replacement of glass powder used is 0%, 25%, and 50% of the composition of the sand. From the results of the analysis it was found that the water absorption capacity of the concrete brick with the addition of glass powder to the mixture of the concrete brick as a substitute for sand in the 0% concrete brick glass powder was 5.13% greater than the variation of 25% glass powder and 17.1% greater than the 50% variation of glass powder. The compressive strength of the concrete brick making with the addition of glass powder as a substitute for sand in the mixture of the concrete brick compressive strength of 25% glass powder is 11.11% better than oncrete brick 0% glass powder and compressive strength of the concrete brick 50% glass powder is better 33.33% than concrete brick 0% glass powder. Based on SNI 03-0349-1989, water absorption and compressive strength on concrete brick with the addition of glass powder as a substitute for sand still meet the requirements